The crystal structure of bis[μ2-(3-(3-(pyridin-2-yl)-1H-pyrazol-1-yl)propanoate-κ2O:N)-bis(2,2′-bipyridine-κ2 N, N′)dicopper(II)]dinitrate, C42H36Cu2N12O10 - Tang Zhiwei; Zheng Ruijuan; Guo Wei; Zhou Jiangcong (Zeitschrift für Kristallographie - New Crystal Structures)
C42H36Cu2N12O10, monoclinic, P21/n (no. 14), a = 11.0161(4) Å, b = 11.8753(5) Å, c = 15.6055(5) Å, β = 95.197(3)°, V = 2033.11(13) Å3, Z = 2, R gt(F) = 0.0398, wR ref(F 2) = 0.0935, T = 293 K.